2021
DOI: 10.1186/s13075-020-02394-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of biosimilar CT-P17 versus reference adalimumab in subjects with rheumatoid arthritis: 24-week results from a randomized study

Abstract: Background To demonstrate equivalent efficacy of the proposed high-concentration (100 mg/ml), citrate-free adalimumab biosimilar CT-P17 to European Union-approved adalimumab (EU-adalimumab) in subjects with active rheumatoid arthritis (RA). Methods This randomized, double-blind phase III study (ClinicalTrials.gov, NCT03789292) randomized (1:1) subjects with active RA at 52 centers to receive CT-P17 or EU-adalimumab 40 mg subcutaneously every 2 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 13 publications
(17 reference statements)
3
48
0
1
Order By: Relevance
“…Patients receiving CT-P17 in period 1 continued CT-P17 treatment in period 2. The ACR20, ACR50 and ACR70 response rates at week 24 were 82.7%, 60.2% and 40.7% in the CT-P17 group and 82.7%, 63.6% and 44.4% in the EU-adalimumab group (95% CI −5.94 to 5.94), 38 which showed similar therapeutic efficacy between CT-P17 and EU-adalimumab.…”
Section: Ct-p17mentioning
confidence: 75%
See 1 more Smart Citation
“…Patients receiving CT-P17 in period 1 continued CT-P17 treatment in period 2. The ACR20, ACR50 and ACR70 response rates at week 24 were 82.7%, 60.2% and 40.7% in the CT-P17 group and 82.7%, 63.6% and 44.4% in the EU-adalimumab group (95% CI −5.94 to 5.94), 38 which showed similar therapeutic efficacy between CT-P17 and EU-adalimumab.…”
Section: Ct-p17mentioning
confidence: 75%
“…37 Kay et al conducted a 52-week multicenter, randomized, double-blind, phase III clinical trial (N=648) to evaluate the efficacy of CT-P17 compared with EU-adalimumab and reported results up to week 24. 38 Moderate-tosevere RA patients were randomized to receive either CT-P17 or EU-adalimumab 40 mg injection every other week until week 24 (period 1). At week 26, patients receiving EU-adalimumab in period 1 were rerandomized either to transition to CT-P17 or to maintain EU-adalimumab treatment until 48 weeks (period 2).…”
Section: Ct-p17mentioning
confidence: 99%
“…Other studies in the CT‐P17 clinical development programme evaluated biosimilarity of CT‐P17 and reference adalimumab administered by PFS 14,15 . Patients with rheumatic disease have indicated a preference for AI over PFS administration of medications 16–20 ; therefore, the availability of an AI device option for CT‐P17 administration could benefit patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in the CT-P17 clinical development programme evaluated biosimilarity of CT-P17 and reference adalimumab administered by PFS. 14,15 Patients with rheumatic disease have indicated a preference for AI over PFS administration of medications [16][17][18][19][20] ; therefore, the availability of an AI device option for CT-P17 administration Limitations of this study include that it was not powered to formally assess safety, so there could be numerical differences in safety findings between groups that may not reflect true differences. Enrolment of both male and female subjects might increase variability in PK findings beyond that explained by differences in body weight, since drug PK profiles can differ between males and females, 37 including those reported for reference adalimumab.…”
Section: Comparability Of Pk Parameters Between Ct-p17 Ai and Ct-p17mentioning
confidence: 99%
See 1 more Smart Citation